Uppbyggnaden av ett foderstatsprogram för dikor - Gudmundsson, Lydia (2005)
The object with this work was to create a simple feeding program for beef cows. Another object was that I could learn more about the properties and functions of Excel and Visual Basic. I used parts of a program I designed a few years ago. This old program was neither user friendly nor had it an appealing layout. Initially I decided how I wanted the new program to appear and on which foundation it should be built. I designed various forms into a spread sheet, such as lists and multiple choice buttons. Using VBA (Visual Basic for Application) I could create macros, which used the information chosen in the lists and with the multiple choices to calculate the feeding requirement or the feeding plan. The macros connect the various forms so that choosing an element in a list or a multiple choice button will advance the user and help him/her through it. The other forms were edited using various alternatives in Excel. I have designed a help manual to make the programme easy to use. I have designed a user friendly feeding program for beef cows. It uses macros, equations and lists in Excel. The program is easy to expand to include other functions, for example a price list of different types of feeds to enable the calculation the cost of a cow's daily feed intake. In the future I can alter the program according the conditions which are current at that time. I have also acquired knowledge about macros, which will enable me to design other programs. I've completed an operational program of forage statistics, which enables one to quickly acquire a feeding plan for a beef cow. In order for the program to work properly it is eminent that one has relevant feeding analyses under the headline "fodermedel". If this is not correct the entire calculation will be totally misleading.